Relationship between Classroom Environment and Student Motivation in Secondary Education in Sudan - Aziz , Abdel (American Journal of Education and Practice, 2024)
Purpose: The aim of the study was to assess the relationship between classroom environment and student motivation in secondary education in Sudan. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: A positive and supportive classroom atmosphere, characterized by clear expectations, engaging teaching methods, and supportive relationships between teachers and students, has been consistently linked to higher levels of student motivation. When students feel valued and respected within their learning environment, they tend to exhibit greater enthusiasm for learning, increased persistence in academic tasks, and higher levels of intrinsic motivation. Conversely, negative aspects of the classroom environment, such as lack of teacher support, unclear expectations, or disruptive peer interactions, can significantly diminish student motivation. Studies indicate that environments perceived as stressful or unsupportive can lead to reduced engagement, decreased academic performance, and higher levels of disengagement among secondary school students. Effective classroom management strategies, including promoting a sense of belonging and autonomy, fostering positive teacher-student relationships, and creating opportunities for student collaboration and decision-making, are crucial in cultivating a motivating learning environment that supports academic success and overall well-being in secondary education. Implications to Theory, Practice and Policy: Self-determination theory, expectancy-value theory and social cognitive theory may be used to anchor future studies on assessing the relationship between classroom environment and student motivation in secondary education in Sudan. In terms of practical implications, educators are encouraged to adopt flexible seating arrangements that offer students autonomy and choice in their learning environments. On a policy level, it is crucial to advocate for investments in school infrastructure and classroom design that support flexible and adaptable learning spaces.